Intrahepatocellular crystal storing mimicking a clinical liver disease during monoclonal gammopathy: report of a case and review of the literature. (2nd January 2020) - Riefolo, Mattia; Malvi, Deborah; Bertuzzi, Clara; Sabattini, Elena; Valente, Sabrina; Pasquinelli, Gianandrea; D'Errico, Antonia; Vasuri, Francesco
ABSTRACT: We present an unusual case of liver involvement in monoclonal gammopathy with generalized crystal-storing histiocytosis (G-CSH). A bone marrow storage disease was diagnosed in a 79-year-old man with monoclonal gammopathy of uncertain significance (MGUS). The patient presented with pleural effusion, an osteolytic lesion of the humerus, and an increase of aspartate transaminase and cholestatic markers that raised the clinical suspect of liver disease. A second bone marrow biopsy confirmed the diagnosis of MGUS with a histiocytic component suggestive for G-CSH. Liver biopsy showed an unremarkable histology, no significant inflammatory infiltrates, and intrasinusoidal foamy histiocytes. PAS and Masson's trichrome stains, showed, in the cytoplasm of both histiocytes and hepatocytes, rod-shaped eosinophilic crystals, which were immunoreactive for kappa light chains. Transmission electron microscopy performed on reprocessed histological sections confirmed the presence of crystals in the hepatocyte cytoplasms. Immunogold labeling intensely stained crystals for kappa light chains. To the best of our knowledge, this is the second case in which an intrahepatocellular crystal storage is described during liver involvement in G-CSH. The present case also suggests that an increase in liver serum enzymes may support the clinical diagnosis of liver CSH in a patient with MGUS.